Antibacterial Activity Test of Elephant ginger (Zingiber officinale Rosc.) Endophytic Fungi Variation of Elephants Against Bacteria That Cause Skin Infections - seniwati seniwati; Laras Aprilia; Rusli Rusli; Tadjuddin Naid (Hasanuddin University, 2020)
Elephant ginger rhizome has the potential as an antibacterial, therefore the research was conducted to test the antibacterial activity of elephant ginger endophytic fungi against bacteria that cause skin infections, determine test bacteria that can be inhibited by elephant ginger endophytic fungi and bioautogram profile for its antibacterial activity. Isolation of endophytic ginger elephant fungi using the direct planting method. Screening of endophytic fungi isolates was placed on the surface of NA medium containing test bacteria Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acne. The screening results obtained were 2 isolates namely isolates which had the highest activity namely IFDRJG03 and IFDRJG04. For IFDRJG03 isolates can inhibit the antibacterial activity of Staphylococcus aureus 25.26 mm, Staphylococcus epidermidis 26.89 mm and Propionibacterium acne 27.12 mm, IFDRJG04 isolates can inhibit the antibacterial activity of Staphylococcus aureus 15.87 mm, Staphylococcus epidisidis 18 and 96 mm. 27.43 mm. Then the TLC-Bioautography test was carried out, the results of IFDRJG03 isolates were obtained using chloroform eluents: methanol (1: 1) had antibacterial activity against Staphylococcus aureus with Rf1 = 0.9 and Rf2 = 0.5, Staphylococcus epidermidis with Rf1 value = 0.8 and Rf2 = 0.5 and Propionibacterium acne with Rf1 value = 0.9 and Rf2 = 0.5 and isolation of IFDRJG04 isolates with ethyl acetate eluent: ethanol: water (8: 2: 1) has antibacterial activity against Staphylococcus aureus Rf1 values = 0.9 Rf2 = 0.7 Rf3 = 0.6, Staphylococcus epidermidis with Rf1 value = 0.7 Rf2 = 0.6, Rf3 = 0.5 and Propionibacterium acne with Rf1 value = 0.9 and Rf2 = 0.7.lephant ginger rhizome has the potential as an antibacterial, therefore the research was conducted to test the antibacterial activity of elephant ginger endophytic fungi against bacteria that cause skin infections, determine test bacteria that can be inhibited by elephant ginger endophytic fungi and bioautogram profile for its antibacterial activity. Isolation of endophytic ginger elephant fungi using the direct planting method. Screening of endophytic fungi isolates was placed on the surface of NA medium containing test bacteria Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acne. The screening results obtained were 2 isolates namely isolates which had the highest activity namely IFDRJG03 and IFDRJG04. For IFDRJG03 isolates can inhibit the antibacterial activity of Staphylococcus aureus 25.26 mm, Staphylococcus epidermidis 26.89 mm and Propionibacterium acne 27.12 mm, IFDRJG04 isolates can inhibit the antibacterial activity of Staphylococcus aureus 15.87 mm, Staphylococcus epidisidis 18 and 96 mm. 27.43 mm. Then the TLC-Bioautography test was carried out, the results of IFDRJG03 isolates were obtained using chloroform eluents: methanol (1: 1) had antibacterial activity against Staphylococcus aureus with Rf1 = 0.9 and Rf2 = 0.5, Staphylococcus epidermidis with Rf1 value = 0.8 and Rf2 = 0.5 and Propionibacterium acne with Rf1 value = 0.9 and Rf2 = 0.5 and isolation of IFDRJG04 isolates with ethyl acetate eluent: ethanol: water (8: 2: 1) has antibacterial activity against Staphylococcus aureus Rf1 values = 0.9 Rf2 = 0.7 Rf3 = 0.6, Staphylococcus epidermidis with Rf1 value = 0.7 Rf2 = 0.6, Rf3 = 0.5 and Propionibacterium acne with Rf1 value = 0.9 and Rf2 = 0.7.